The historical Jesus and the temple: memory, methodology, and the Gospel of Matthew - Barber, Michael Patrick (Cambridge University Press, 2023)
In this book, Michael Patrick Barber examines the role of the Jerusalem temple in the teaching of the historical Jesus. Drawing on recent discussions about methodology and memory research in Jesus studies, he advances a fresh approach to reconstructing Jesus' teaching. Barber argues that Jesus did not reject the temple's validity but that he likely participated in and endorsed its rites. Moreover, he locates Jesus' teaching within Jewish apocalyptic eschatology, showing that Jesus' message about the coming kingdom and his disciples' place in it likely involved important temple and priestly traditions that have been ignored by the quest. Barber also highlights new developments in scholarship on the Gospel of Matthew to show that its Jewish perspective offers valuable but overlooked clues about the kinds of concerns that would have likely shaped Jesus' outlook. A bold approach to a key topic in biblical studies, Barber's book is a pioneering contribution to Jesus scholarship.